HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM TABLET TAMBAH DARAH PADA IBU HAMIL DI PUSKESMAS BANYUGLUGUR KABUPATEN SITUBONDO - Kristiana, Ni Made Diana; Yuliana, Wahida; Hikmawati, Nova (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Family support in the form of attention, emotions, information, advice, motivation and understanding provided by a group of family members to other family members is needed in an effort to prevent anemia and increase adherence to taking Fe tablets. The purpose of this study was to determine the relationship between family support and adherence to taking Fe tablets at the Banyuglugur Health Center The design of this study was cross sectional. The population in this study was all pregnant women in the Banyuglugur health center as many as 76 pregnant women. The sample was all 63 pregnant women in Banyuglugur Health Center using purposive sampling techniques.The instruments used showed family support questionnaires and MCH book observation sheets. The results of the study, pregnant women with widle family support are obedient to drink Fe Tablet. While pregnant women with low family support many do not obey. Based on the chi square statistical test, it was known that the P Value value is 0.000 with α 0.05. Because of the significance value of < α, H0 is rejected and H1 is accepted, which means that there is a correlation between family support and adherence in taking Fe tablets at the Banyuglugur Health Center. It is hoped that the results of this study can be used as input for people who have babies with constipation to consume Fe tablets.